Meta-analysis of recommended digestible lysine levels for primiparous lactating sows - Garcia, Amélia Maria Lima; Kiefer, Charles; Nascimento, Karina Márcia Ribeiro de Souza; Lehnen, Cheila Roberta; Hauschild, Luciano [UNESP]; Silva, Camilla Mendonça; Alencar, Stephan Alexander da Silva; Rodrigues, Gabriela Puhl (FapUNIFESP (SciELO), 2020)
A meta-analysis was carried out to evaluate the recommended levels of digestible lysine and its influence on the productive performance of primiparous lactating sows. The database consisted of 26 publications, 138 diets and 3,820 sows was developed from articles on the association between, lysine, crude protein and lactating primiparous sows. The digestible lysine levels of the studies ranged from 0.22 to 1.43% with average values of 0.85% digestible lysine in the diet, with consumption of 41.25 g day-1. The digestible lysine intake of sows was positively correlated (P<0.05) with feed intake, essential amino acids, crude protein, metabolizable energy, body weight loss sows, milk production, number and weight of piglets at weaning. Digestible lysine intake showed negative correlation (P<0.05) with backfat thickness at weaning and weaning to oestrus interval. It was observed a quadratic effect (P<0.01) of body weight loss sow and daily weight gain of piglets and a quadratic effect (P<0.01) in the weight of piglets at weaning due to increased dietary lysine level. The level of 1.04% of digestible lysine indicates less weight loss sows. The greater weight of piglets at weaning and increased daily weight gain of piglets was verified with the addition of 1.30 and 1.07% digestible lysine in the diet, respectively.
Meta-análise dos níveis de lisina digestível recomendados em dietas de porcas primíparas lactantes
Keywords: Amino acids; Nutrition; Parity order; Sows